Antenatal magnesium sulphate administration for fetal neuroprotection: a French national survey - Clément Chollat; Lise Le Doussal; Gaëlle de la Villéon; Delphine Provost; Stéphane Marret (BMC, 2017)
Abstract Background Magnesium sulphate (MgSO4) is the only treatment approved for fetal neuroprotection. No information on its use is available in the absence of a national registry of neonatal practices. The objective of our study was to evaluate the use of MgSO4 for fetal neuroprotection in French tertiary maternity hospitals (FTMH). Methods Online and phone survey of all FTMH between August 2014 and May 2015. A participation was expected from one senior obstetrician, one senior anaesthetist and one senior neonatologist from each FTMH. Information was obtained from 63/63 (100%) FTMH and 138/189 (73%) physicians. Use of MgSO4 for fetal neuroprotection, regimen and injection protocols, reasons for non-use were the main outcome measures. Results 60.3% of FTMH used MgSO4 for fetal neuroprotection. No significant difference was observed between university and non-university hospitals or according to the annual number of births. Protocols differed especially in terms of the maximum gestational age (3% <28 WG, 71% <33 WG, 18% <34 WG and 8% < 35 WG). Eighty seven percent of centers using MgSO4 prescribed retreatment when necessary, but according to non-consensual modalities in terms of number of treatments or between-treatment intervals. Injections and monitoring were mostly performed in the delivery room (97%) but also in the recovery room in one half of hospitals. Lack of experience (52%), absence of a written protocol (49%) and national guidelines (46%) were the reasons most commonly reported to explain non-use of MgSO4 as a neuroprotective agent. Conclusions Sixty percent of FTMH used MgSO4 for fetal neuroprotection, but according to heterogeneous regimens. National guidelines could allow standardization of practices and better MgSO4 coverage.